(3GdJQHjI GdHjFjI aj GdWahdI GdeHcQI hJWHjbGJgG (B/s - (3LGO, efi eMeO Ydjs ((3YeGf, GdCQOf (B:s (3OGQ GdeSjQI ddfTQ hGdJhRjY hGdWHGYI,s, 2004)
(3EYOGO GdWad ddMjGI GdGLJeGYjI(B.s
(3HHdjhLQGajI (B: (3U(B. 373-376.s
Keywords: (3GdJQHjI GdHjFjIs; (3MeGjI GdHjFIs -- (3OQGSI hJYdjes